Mubadalah's Perspective Family Education In Realizing The Maslahah Family - Indriana, Dina; Ilzamuddin, Ilzamuddin; Muhajir, Muhajir; Ngaisah, Siti; Ubaidillah, Ubaidillah (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
This study aims to apply the concept of maslahah family education in everyday life, emphasizing the importance of educational values and good morals in every family interaction. Maslahah family education seeks to build a harmonious family by instilling positive values that can serve as a guide in facing various situations and challenges in life. Each family member is expected to apply these values in real actions, creating an environment conducive to personal growth and development. In dealing with family problems, it is important for each member to discuss and deliberate in order to reach a mutual agreement. Good communication is key in this process, where every opinion is valued, and individual egos do not become obstacles in finding solutions. The mubadalah approach, which emphasizes equality and justice, can be a strong foundation in resolving family conflicts. By deliberating and prioritizing common interests, family issues can be effectively resolved. This study uses a field qualitative method, recording various problems encountered in the field and analyzing them descriptively using supportive references. The results show that the approach of deliberation, discussion, and good communication can resolve family issues without prioritizing personal egos. The application of the maslahah family concept in society can be a solution to maintain the integrity of the household, while the mubadalah approach can be used as an effective method in finding solutions to various family problems.